Re-updating the taxonomy of Kluyvera genus for a better understanding of CTX-M β-lactamase origin - Rodríguez, María Margarita (2024)
The taxonomic definitions within the Kluyvera genus are still unclear, asseveral deposits might belong to misidentified species or genus or genome assemblies comprehend large indeterminate nucleotide zones. In this study, we performed a comparative phylogenomic analysis of Kluyvera chromosomes and other selected Enterobacterales. We also included the genomic analysis of chromosomal blaCTX-M/KLUfrom Kluyvera isolates and assigned the plasmid-encoded blaCTX/M genes. The studyallowed us to propose a new Kluyvera genomospecies and to better define Kluyvera genomosp. 5. Two new CTX-M sub-groups could also be suggested. Even if no chromosomal blaCTX-M/KLU gene can be found in K. intermedia and Kluyvera genomosp. 6, accurate identification can be achieved by using these gene sequences in the remaining strains.